If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -1) = 14 Reorder the terms: -2(-1 + x) = 14 (-1 * -2 + x * -2) = 14 (2 + -2x) = 14 Solving 2 + -2x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2x = 14 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = 14 + -2 -2x = 14 + -2 Combine like terms: 14 + -2 = 12 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| 16X^2=25 | | -7(5-4x)=189 | | 3x+0.6=x | | 35=5 | | 2x^2+1x-3=0 | | 35=-5 | | 4(x-6)=-52 | | 2(x+2)=-14 | | 3(x+9)=45 | | 2(x+2)=-8 | | 81x^2=25 | | 5(x-3)=-50 | | 3(x-8)=-45 | | 9x^2=16 | | 5(x+5)=40 | | 25x^2=36 | | 3(x-9)=-24 | | 5(x+7)=50 | | 15x-3(x+6)=6 | | 4.2(x+3)=27 | | -9x+2.2=-3x+7.0 | | 1.333w-12=.666w | | -5x+2.5=-3x+1.1 | | -3x-3.9=-7x-2.7 | | x^2(9x+5)(9x-5)=0 | | 8x-1.2=-9x+14.1 | | 5x+2=8x+19 | | 8x-1.2=-9x+14.4 | | 180=(x+20)+60+3x | | 8x+2.6=-5x-3.9 | | 3x^2+26x=-16 | | 6x+3.6=3x+4.8 |